Efficacy and Safety of Endoscopic Esophageal Dilatation in Paediatric Patients with Esophageal Strictures in Low Middle-Income Country - Asghar, Taram; Malik, Nayyab Junaid; Atif, Muhammad; Malik, Huma; Aamir, Muhammad Uzair; Chaudhry, Muhammad Amjad (Biological and Clinical Sciences Research Journal, 2025)
Pediatric esophageal strictures are a significant health concern in lower-middle-income countries (LMICs), particularly in Pakistan, due to factors such as corrosive ingestion and congenital anomalies. Endoscopic esophageal dilatation (EBD) offers a minimally invasive and cost-effective solution, but its outcomes in LMIC settings require further evaluation. Objective: To assess the efficacy and safety of endoscopic esophageal dilatation in pediatric patients with esophageal strictures in a lower-middle-income setting. Methods: This prospective observational study was conducted at the Department of Pediatric Surgery, Pakistan Institute of Medical Sciences, Islamabad, from October 2024 to March 2025. A total of 84 pediatric patients aged 6 months to 14 years with confirmed esophageal strictures underwent EBD using Savary-Gilliard bougies or TTS balloon dilators. The primary outcomes were technical and clinical success, while the secondary outcomes included the number of sessions and complications. Data were analyzed using SPSS version 26, with a p-value <0.05 considered significant. Results: The mean age of the patients was 6.2 ± 3.4 years; 54.8% of the patients were male. Corrosive ingestion (48.8%) was the most common etiology. The technical success rate was 100%, and clinical success (symptom relief) was achieved in 90.5% of cases. The average number of dilatation sessions required was 3.6 ± 1.2, with a median interval of 14 days. Minor complications occurred in 27.4% of patients, while major complications (perforation) were observed in 2.4% and managed conservatively. A significant association was found between etiology and the number of sessions required (p = 0.003), with corrosive strictures requiring the most sessions. Conclusion: Endoscopic esophageal dilatation is a highly effective and safe treatment for pediatric esophageal strictures in resource-limited settings. Its excellent technical and clinical success rates, coupled with a low complication profile, make it a viable first-line therapy, especially for LMICs like Pakistan.